2022
DOI: 10.3390/atmos13040526
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Multi-Model Ensemble Forecasting Accuracy between Equal- and Variant-Weight Techniques

Abstract: Previous studies on multi-model ensemble forecasting mainly focused on the weight allocation of each model, but did not discuss how to suppress the reduction of ensemble forecasting accuracy when adding poorer models. Based on a variant weight (VW) method and the equal weight (EW) method, this study explored this topic through theoretical and real case analyses. A theoretical proof is made, showing that this VW method can improve the forecasting accuracy of a multi-model ensemble, in the case of either the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Based on the performance of the 12 S-curve models, we assign weights that are individual for each municipality and use the weights to combine the probabilistic projections. We derive the calculation of weights from methods of ensemble weather forecasting where the use of inverse error variance outperforms equal weighting ( 67 , 68 ). The mean squared WIS acts as the error variance in our case.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the performance of the 12 S-curve models, we assign weights that are individual for each municipality and use the weights to combine the probabilistic projections. We derive the calculation of weights from methods of ensemble weather forecasting where the use of inverse error variance outperforms equal weighting ( 67 , 68 ). The mean squared WIS acts as the error variance in our case.…”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, some researchers have combined the output of several NWP models to increase their forecast quality, known as the multi-model ensemble system [25,26]. Wei et al (2022) compared the forecasting accuracy of equal and variant weight techniques to create a multi-model ensemble forecast provided by the National Meteorological Information Center of China. They concluded that the variant weight method produced more accurate temperature forecasts [27].…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al (2022) compared the forecasting accuracy of equal and variant weight techniques to create a multi-model ensemble forecast provided by the National Meteorological Information Center of China. They concluded that the variant weight method produced more accurate temperature forecasts [27]. Medina et al (2018) developed a multi-model ensemble system to forecast reference evapotranspiration by combining the models of the European Centre for Medium-Range Weather Forecasts (ECMWF) and the United Kingdom Meteorological Office (UKMO) using the linear regression model.…”
Section: Introductionmentioning
confidence: 99%